Persepsi Konsumen terhadap Kualitas Tempe di Pasar Lokal, Nasional, dan Internasional: Consumer Perceptions of the Tempe Quality in Local, National, and International Markets - Angel Kurnilah Fitri; Dimas Wahyu Ekawananto; Made Astawan; Saraswati Saraswati; Tutik Wresdiyati; Wanida Tewaruth Chitisankul; Andi Early Febrinda; Songsak Wattanachaisaereekul (Amerta Nutrition, 2025)
Background: Tempe, a fermented soybean product produced with Rhizopus spp., contains nutrients and bioactive compounds beneficial for health. Today's awareness of healthy living is driving increased consumption, production, and marketing of tempe. Several tempe producers are capitalizing on this opportunity by producing tempe on a larger scale, with greater hygiene, and with higher levels of marketing. Tempe is currently sold in local, national, and international markets. Research on consumer perceptions of tempe quality in local, national, and international markets has not yet been conducted. Objectives: The research analyzed consumer perceptions of the tempe quality circulating in the local Bogor market, national modern markets, and international markets (exports). Methods: Data collection was conducted through a Google Form, involving 292 respondents aged 25-55. Respondents were asked to assess the quality of tempe sold at three marketing levels: the local Bogor market, the national modern market, and the international (export) market. Data were analyzed using one-way Analysis of Variance (ANOVA) and the Duncan Multiple Range Test (DMRT) post hoc test. Results: Respondents generally preferred white tempe for its dense texture and distinctive aroma. The ranking test results showed that the three types of tempe differed significantly (p-value<0.05) in overall appearance, packaging design, and label completeness. The appearance of sliced ​​tempe from national and international markets did not differ significantly (p-value>0.05). Conclusions: The visual appearance of tempe from local, national, and international markets differed significantly (p-value<0.05). Tempe from national and international markets had a significantly better overall appearance, packaging design, and label completeness (p-value<0.05) than tempe from local markets. The study analyzed the quality of tempe in local, national, and international markets, and tempe producers can use the results to improve tempe quality standards and expand their market.